Urodnjavanje bez roda? Analiza gender mehanizama u odabranim lokalnim zajednicama Bosne Hercegovine / Gender Mainstreaming Without Gender? Analysis of Gender Equality Mechanisms in Selected Local Communities of Bosnia and Herzegovina - Popov-Momčinović, Zlatiborka; Ždralović, Amila (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
Gender equality is a democratic and civilizational standard, and mechanisms to implement gender mainstreaming have been established in many countries around the world, including Bosnia and Herzegovina. International mechanisms and women's civil society organizations are the main carriers of these changes, but the real impact of gender mainstreaming depends on the ability of institutions and the commitment of policy makers to move gender from the margins to the center in setting public policy at all levels of government. Unfortunately, across globally, the norm and practice diverge, especially at the local level. In the countries of the Western Balkans, these problems are even more pronounced and insufficiently articulated in academic research. Therefore, this paper analyzes the results of a survey conducted in local communities in Bosnia and Herzegovina. The research included an analysis of legal provisions at the local level and interviews with relevant stakeholders (women activists and members of local equality commissions). The analysis shows that gender equality is addressed in a fragmented and inconsistent manner, that it is not adequately addressed in local documents, and that local gender mechanisms (commissions for gender equality) have been formed to fulfill a formal obligation. In communities with no profiled women's organizations, the situation is even worse when it comes to the possibility of monitoring and improving the work of these mechanisms.